Excellence in Family Paediatricians: the FIMP-MCRN (Medicines for Children Research Network) becomes a member of ENPR-EMA (European Network of Paediatric Research at the European Medicines Agency) - Napoleone Ettore (BMC, 2011)
Abstract One of the objectives of the Paediatric Regulation (EC) No 1901/2006, is to foster high quality ethical research on medicinal products to be used in children. To achieve this objective, the EMA is responsible for developing a European paediatric network of existing national and European networks and centres with specific expertise in research and clinical trials relating to paediatric medicines. The purpose of this article is to disseminate knowledge of the structure and goals of ENPR-EMA and to highlight the cultural and organizational difficulties for its implementation. Following the publication of research quality requirements, a set of recognition criteria, which have to be fulfilled to become a member of ENPR-EMA were agreed. So far, 32 networks and centres (of 62 identified networks) submitted self-assessment reports indicating whether or not they fulfill the agreed minimum criteria. Sixteen networks (26% of 62 identified networks) fulfilled all minimum criteria and became therefore members of ENPR-EMA. The Family Paediatricians Medicines for Children Research Network (FIMP-MCRN), established with the aim of developing competence, infrastructure, networking and education for paediatric clinical trials, became member of the ENPR-EMA responding satisfactorily to all the points of the self-assessment report.